Cardiac amyloidosis: a review - Baska, Aleksandra; Kazik, Jakub; Bojczuk, Daria; Racinowski, Mariusz; Leis, Kamil; Mazur, Ewelina; Kałużny, Krystian; Gałązka, Przemysław (Journal of Education, Health and Sport, 2019)
Cardiac amyloidosis is a type of amyloidosis in which one of the affected organs is the heart. The disease is characterized by the formation of protein aggregates between the cells of the organ, namely amyloid, which disables its function. The following types of amyloidosis can be distinguished: systemic senile amyloidosis (wild-type ATTR), light chain amyloidosis (AL) and hereditary transthyretin-related amyloidosis. The symptoms include, e.g., systolic dysfunction or arrhythmia. The treatment is focused on the therapy with melphalan and, additionally, stem cells transplant and chemotherapy with dexamethasone or cyclophosphamide. In the advanced stage of the disease, a heart transplant is necessary. The diagnosis is made on the basis of laboratory testing, electrocardiogram changes, and echocardiography.